Kewenangan KUA Kecamatan dan Pengadilan Agama Dalam Perkara Perubahan Biodata Akta Nikah - Muhammad Sangidun; Roykhatun Nikmah (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
This study aims to examine the authority of the District Office of Religious Affairs (KUA) and the Religious Courts in changing marriage certificate biodata. To change the biodata on the marriage certificate, it should be enough to do it at the District KUA in accordance with the provisions in PMA Number 20 of 2019 and there is no need to go through the determination of the Religious Courts because it is not legally mandated in Law Number 50 of 2009. Meanwhile, the judges of the Cilacap Religious Court granted the request for a change in the marriage certificate biodata on the grounds that it had previously submitted to the KUA but was rejected. This is not in accordance with PMA Number 20 of 2019 and Law Number 50 of 2009 it can be said that the KUA rejects cases under its authority and the Religious Courts handle cases outside its authority. With the qualitative field method, the data were collected through interviews and documentation and analyzed descriptively. The findings in the study in the form of the KUA's refusal to change the marriage certificate biodata were because the Petitioner did not fulfill the administrative requirements in the form of a birth certificate, the case of changing the marriage certificate biodata at the Cilacap Religious Court in 2020 was 309 cases, and the judge granted the request based on the provisions of Article 49 Law Number 50 of 2009. The conclusion of this research is that the KUA and the Religious Courts are both authorized to change the marriage certificate biodata, the authority attached to the KUA is absolute authority as stated in PMA Number 20 of 2020 while the Religious Courts are an expansion of authority in article 49 of the Law. Law Number 50 of 2009 because it is included in the case of the marriage sector. Abstrak Penelitian ini bertujuan untuk meneliti kewenangan Kantor Urusan Agama (KUA) Kecamatan dan Pengadilan Agama dalam mengubah biodata akta nikah. Untuk mengubah biodata pada akta nikah seharusnya cukup dilakukan di KUA Kecamatan sesuai dengan ketentuan dalam Peraturan Menteri Agama Nomor 20 Tahun 2019 dan tidak perlu melalui penetapan Pengadilan Agama sebab secara limitatif bukan merupakan kewenangannya yang diamanatkan dalam Undang-Undang Nomor 50 Tahun 2009. Sedangkan hakim Pengadilan Agama Cilacap mengkabulkan permohonan perubahan biodata akta nikah dengan alasan sebelumnya telah mengajukan ke KUA akan tetapi ditolak. Hal ini tidak sesuai dengan Peraturan Menteri Agama Nomor 20 Tahun 2019 dan Undang-Undang Nomor 50 Tahun 2009.  Dapat dikatakan KUA menolak perkara yang menjadi kewenangannya dan Pengadilan Agama menangani perkara diluar kewenangannya. Temuan dalam penelitian berupa penolakan KUA mengubah biodata akta nikah adalah karena Pemohon tidak melengakpi syarat administratif berupa akta kelahiran, perkara perubahan biodata akta nikah di Pengadilan Agama Cilacap pada tahun 2020 sebanyak 309 perkara, serta hakim mengkabulkan permohonan tersebut berdasarkan ketentuan pasal 49 Undang-Undang Nomor 50 Tahun 2009. Simpulan dari penelitian ini adalah KUA dan Pengadilan Agama sama-sama berwenang mengubah biodata akta nikah, kewenangan yang melekat pada KUA merupakan kewenangan mutlak sebagaimana disebutkan dalam Peraturan Menteri Agama Nomor 20 Tahun 2019 sedangkan pada Pengadilan Agama merupakan perluasan kewenangan dalam pasal 49 Undang-Undang Nomor 50 Tahun 2009 sebab termasuk dalam perkara bidang perkawinan.